Business Model for Traditional Performing Arts - Anggraeni, Ade Irma (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
The urgency of this research stems from the phenomenon of local wisdom-based performing arts currently being a major concern in the development strategies of various related institutions, including the Ministry of Tourism and Creative Economy. Traditional performing arts with various elements of art involved in it including music, dance, karawitan and puppetry have the potential to be commercialised and combined with various contemporary arts to increase attractiveness for consumers. Performing arts as a subsector of the creative economy is expected to be one of the components of the economic driver through the path of non-natural tourist destinations in each region. However, until now, traditional performing arts with distinctive values have not been fully seen as an option for tourists at the local, national and international levels. This is also experienced by cultural performing arts in Banyumas. Based on the framework of push-pull factors of tourism, traditional performing arts still require management both from the artist side and from the consumer perception side. This research aims to develop a business model to support the commercialisation of cultural performing arts so that it can become one of the choices of tourist destinations in Banyumas Regency. There are several concepts used in this business model including talent scouting, experiential marketing and learning management system. Talent scouting is needed to develop the value of performing arts through developing the capacity of talents in the field of performing arts, namely art workers. Digitised experiental marketing is used to produce actual performing arts services that can be experienced directly by consumers. Learning management system is the basis for the development of tools that can bring together art activists, consumers and cultural influences.